Regulation of gene expression by growth hormone. (1st May 2020) - Rotwein, Peter
Abstract: Growth hormone (GH) plays a pivotal role in many physiological processes in humans, and in other mammalian and non-mammalian vertebrate species, through actions on somatic growth, tissue development and repair, and intermediary metabolism. This review will focus on mechanisms of GH actions on gene expression, primarily from the perspective of the genes that encode proteins stimulated by GH to regulate somatic growth, especially insulin-like growth factor 1 (IGF-I), but also others that are induced or repressed by GH. Topics to be discussed will include a brief overview of GH-mediated signal transduction pathways and how these cascades alter the functions of responsive transcription factors, with a specific focus on STAT5B, a key member of the signal transducers and activators of transcription family, characterization of essential GH-regulated genes, and elucidation of mechanisms of their regulation from biochemical, genetic, and genomic perspectives. Highlights: The transcription factor, STAT5B, plays a central role in GH-regulated gene expression. GH receptor-activated STAT5B binds to enhancer elements in chromosomal DNA of GH-target genes to control gene activation. The Igf1 locus in mammals encodes multiple GH-regulated STAT5B-binding transcriptional enhancers. Mechanisms of Igf1 gene regulation by GH in non-mammalian vertebrates are unknown. Future studies should focus on individual variation of transcriptional responses to GH in human health and disease.